Non-Voluntary Passive Euthanasia should be Legalized in Sri Lanka - Vidanapathirana, M. (Proceedings of CFPSL 15th Annual Academic Sessions 2016/17, 2016)
Attached

Euthanasia is the practice of intentionally ending a life in order to relieve pain and suffering. However, the general understanding of euthanasia is the bringing about of a good death or 'mercy killing', where one person ends the life of another person, for his or her sake. To justify such acts and circumstances, the ethical principles applied frequently are the “right to die” and “right to terminate life”. When the consent of the person is considered* it can be classified in to three; voluntary, nonvoluntary or involuntary, and based on the method of application, it is classified in to active or passive euthanasia. When a person knowingly declares the wish to end his life or specially requests that his life be terminated it is termed as voluntary euthanasia. [2] This decision can be done at the time of the illness or in advance by way of “living wills or advance directives”. When considering ‘non-voluntary euthanasia’, the patient leaves the ‘decision making capacity’ with a physician or a relation by proxy. [3] This is called “Suicide by proxy”. If no prior proxy, relatives and physicians can take a court order to terminate life for the best interest of the patient and to die with dignity. ‘Involuntary euthanasia’ is performed against the will of the patient and the physician takes the decision on his own to terminate the life of the patient without a personal or proxy invitation and this amounts to homicide, whether active or passive. [4] When considering ‘active euthanasia’, death is brought about by an act of commission by the physician. Whereas, in ‘passive, euthanasia’^ the death is brought about by an act of omission by the physician. Voluntary refusal of treatment or voluntary refusal of food and fluids (VRFE) by a patient is , ‘voluntary passive euthanasia’. Further, physician-assisted suicides (PAS), are also a type of ‘voluntary passive euthanasia’. In physician-aSsisted suicide, the physician should play a passive role rather than active. In some instances, when they play an active role, it turns in to ‘voluntary active euthanasia’, which is illegal and unethical. Withdrawal of treatment in a terminally ill patient on proxy consent or court order is ‘nonvoluntary passive euthanasia. Anthony David Tony Bland was in persistent vegetative state for four years. He became the first patient in English legal history to be allowed to die by the courts through the withdrawal of life-prolonging treatment. ABSTRACT BOOK - CFPSL 15>h Annual Academic Sessions 2016/17 Non-voluntary active euthanasia is illegal in almost all countries in the world. The non-treatment of a treatable condition by leaving ‘Do not resuscitate (DNR) orders’ is 'involuntary passive euthanasia’. Since it is involuntary, it is unethical and also amounts to homicide. Involuntary active euthanasia is also illegal in all countries in the world. In In contrast, human euthanasia has been criminalized in Mexico, Thailand and the Northern Territory of Australia. Further, none of these methods of euthanasia, whether active or passive, can be practiced in Sri Lanka. Why euthanasia should be legalization in Sri Lanka? To up hold the rights of the terminally ill patients and allow them to die with dignity. Otherwise, physicians misuse euthanasia and do illegal and unethical malpractices such as DNR orders. Voluntary passive euthanasia (Physician assisted suicide) is legal in Switzerland, Germany, Japan, Albania and some US states (Washington, Oregon, Vermont, New Mexico, Montana, and California). However, why we should not legalize PAS in Sri Lanka? Because, doctors can misuse this. Doctors can end the lives of patients after making a false judgment that their lives are of no value - and claim that they are Simply acting in their patients' best interests", This is called medical : paternalism [10]. : Voluntary active euthanasia is illegal in all the Countries in the world. Since active euthanasia is illegal and unethical, cannot be considered for legalization. Non-voluntary active euthanasia is practiced only in the Netherlands, Belgium, Luxemburg and 1 Switzerland. Since active euthanasia is illegal and unethical it cannot be considered for legalization. Involuntary passive euthanasia such as DNR orders, though practiced, is illegal and unethical. Since it is involuntary, and cannot be consider for legalization. Involuntary active euthanasia is the worse form of euthanasia because both involuntariness and active involvement are illegal and unethical and cannot be considered for legalization. Decriminalizing of non-voluntary passive euthanasia is being debated ewUessly. However, in non-voluntary passive euthanasia, the medical paternalism is minimal. Because it is done on patient’s proxy consent or court order. Unlike in living wills, proxy is not directly related to ending of life, it is to take relevant decisions if incapacitate. When it is written to doctors, decisions are v taken for the best interest of the patient. Further, it is legalized in India (since 2011), England, Albania, Hungary and many parts of the United State. Therefore, in conclusion, to prevent illegal unethical practices of euthanasia, non-voluntary , passive euthanasia should be considered for legalization in Sri Lanka.